Controlling dispersity in aqueous atom transfer radical polymerization: rapid and quantitative synthesis of one-pot block copolymers. Issue 43 (21st October 2021) - Wang, Hyun Suk; Parkatzidis, Kostas; Harrisson, Simon; Truong, Nghia P.; Anastasaki, Athina
Abstract : The dispersity of polymers is efficiently controlled in aqueous atom transfer radical polymerization by modulating the reversible dissociation of the bromide ion from the copper deactivator. Abstract : The dispersity ( Đ ) of a polymer is a key parameter in material design, and variations in Đ can have a strong influence on fundamental polymer properties. Despite its importance, current polymerization strategies to control Đ operate exclusively in organic media and are limited by slow polymerization rates, moderate conversions, significant loss of initiator efficiency and lack of dispersity control in block copolymers. Here, we demonstrate a rapid and quantitative method to tailor Đ of both homo and block copolymers in aqueous atom transfer radical polymerization. By using excess ligand to regulate the dissociation of bromide ions from the copper deactivator complexes, a wide range of monomodal molecular weight distributions (1.08 < Đ < 1.60) can be obtained within 10 min while achieving very high monomer conversions (∼99%). Despite the high conversions and the broad molecular weight distributions, very high end-group fidelity is maintained as exemplified by the ability to synthesize in situ diblock copolymers with absolute control over the dispersity of either block ( e.g. low Đ → high Đ, high Đ → high Đ, high Đ → low Đ ). The potential of our approach is further highlighted by the synthesis of complex pentablock and decablock copolymers without any need for purification between the iterative block formation steps. Other benefits of our methodology include the possibility to control Đ without affecting the M n, the interesting mechanistic concept that sheds light onto aqueous polymerizations and the capability to operate in the presence of air.